The Meaningfulness of The Lives of Farmers who Preserve Traditional Folk Dances: A Case Study in Village X, Samiran, Selo, Boyolali - Happy Listya Retnaningrum; Wiwien Dinar Pratisti (Universitas Muhammadiyah Surakarta, 2025)
Living as a farmer located on the slopes of Mount Merapi where access is not easy to reach and some difficulties that must be faced as a farmer. However, from all the difficulties, farmers in Village X in Selo District, Boyolali choose to fill their free time by practicing dancing. For them, dancing is an activity to relieve boredom. From the difficulties they have, they continue to preserve the arts with totality and selflessly. The purpose of this study was to determine the meaning of life of folk dance artists in Village X. This study involved 3 people who were dancers at Community X. Respondents who work as farmers who often dance in Village X with an age of over 25 years, practice and perform dance performances for more than 10 years. This qualitative research uses a qualitative descriptive approach. This study uses a semi-structured interview method. The attitude of religiosity is reflected in the results of the study, namely the shortcomings of farmers, they are still grateful and try to provide benefits to others through folk dance arts. Dancing is also an activity that makes them feel happy because it can determine their own interests and realize the potential they have so that doing anything related to art can be done totally and selflessly. Folk dancers have hopes from what they have done for their next life. Supported by their experience in art in the village, respondents have an attitude of mutual cooperation and a sense of belonging to develop dance art. Positive attitudes such as optimism and fighting for art that exist in respondents make respondents face problems with full confidence and calm.